Donald Davidson on truth, meaning, and the mental - Preyer, Gerhard (Oxford : Oxford University Press, 2012)
A reappraisal of Donald Davidson's influential philosophy of thought, meaning, and action. Twelve specially written essays by leading philosophers in the field illuminate a range of themes and problems relating to these subjects, and engage in particular with Ernie Lepore and Kirk Ludwig's interpretation of Davidson's thought.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Davidson, Donald, -- 1917-2003.; Truth; Meaning (Philosophy); Act (Philosophy)